Basin‐scale approach needed for Yangtze River fisheries restoration. Issue 4 (14th March 2022) - Jin, Binsong; Winemiller, Kirk O.; Ren, Wenwei; Tickner, Dave; Wei, Xiaohua; Guo, Li; Li, Qin; Zhang, Hui; Pompeu, Paulo Santos; Goichot, Marc; Wang, Sikai; Shen, Ruichang; et al.
Abstract: The Yangtze River contains the highest fish diversity and most important inland fishery resources in China, but its biota and ecosystem services face an uncertain future. The river and its basin have undergone vast changes from centuries of human impacts, and fish stocks are in a particularly dire situation. A complete 10‐year moratorium on commercial fishing within the entire Yangtze River was implemented starting in January 2021. By itself, the ban on fishing will unlikely guarantee full recovery. We conclude that multiple human impacts to the basin and its fish stocks require multidisciplinary strategies implemented at the whole basin scale for effective conservation.